1996
DOI: 10.1111/j.1472-765x.1996.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Escherichia colito acid habituation conditions sensitizes it to alkaline stress

Abstract: Escherichia coli transferred from pHo 7.0 to pHo 5.5 or 6.0 became alkali-sensitive by a rapidly induced phenotypic response. Alkali sensitization was reduced at pHo 5.0 and virtually abolished at pHo 6.5. The response was triggered by cytoplasmic rather than external or periplasmic acidification and de novo protein synthesis was needed. Alkali sensitivity failed to appear at pHo 5.5 plus DNA gyrase inhibitors and was markedly reduced by himA, himD, hns, ompC and nhaA lesions. A tonB deletion mutant showed alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Alkali sensitization after exposure to acidic conditions is also thought to be an EIC-mediated process (Rowbury & Hussain, 1996). Cells of E. coli that were transferred from broth at pH 7.0 to broth at pH 5.5 and then challenged at pH 9.5 or 9.75 for 30 min survived in lower numbers than cells not exposed to pH 5.5 before exposure to alkaline pH.…”
Section: Extracellular Inducing and Sensing Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali sensitization after exposure to acidic conditions is also thought to be an EIC-mediated process (Rowbury & Hussain, 1996). Cells of E. coli that were transferred from broth at pH 7.0 to broth at pH 5.5 and then challenged at pH 9.5 or 9.75 for 30 min survived in lower numbers than cells not exposed to pH 5.5 before exposure to alkaline pH.…”
Section: Extracellular Inducing and Sensing Componentsmentioning
confidence: 99%
“…Chloramphenicol inhibited the development of alkali sensitivity, indicating that protein synthesis is needed to generate alkali-sensitive ESC. There may also be a role for the sodium/hydrogen ion transporter protein, NhaA, because E. coli mutants not expressing NhaA have very little alkali sensitivity (Rowbury & Hussain, 1996). Alkali sensitivity of cells after exposure to acidic conditions may be unexpected because genes that express tolerance to both acidic and alkaline conditions are dependent upon the same sigma factor (Slonczewski & Foster, 1996).…”
Section: Extracellular Inducing and Sensing Componentsmentioning
confidence: 99%
“…The bacterial strains used here were derivatives of Escherichia coli K12 and have been described previously by Rowbury and Hussain (1996). They were as follows: strain 1829 (trp, lac), strain 1829-Amp R1 (1829 hns), strain 1829-Kan R1 (1829 fur) and strain 1829-Tet R1 (1829 himA).…”
Section: Organisms and Growth Conditionsmentioning
confidence: 99%
“…In addition, however, the levels of alkali tolerance of cultures are also influenced by prior growth at acidic pH. Over a narrow pH range (5·5-6·0), exposure to acidity rapidly leads to alkali sensitization, a process dependent on H-NS, IHF and Fur (Rowbury and Hussain 1996). The present study is on such alkali sensitization and it is reported here that extracellular components needed for sensitization, including a very heat-resistant protein, accumulate at pH 5·5; effects of lesions in himA, hns and fur on the formation of these components are described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation